EvoLearner: Learning Description Logics with Evolutionary Algorithms - Heindorf, Stefan; Blübaum, Lukas; Düsterhus, Nick; Werner, Till; Golani, Varun Nandkumar; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (WWW)
Classifying nodes in knowledge graphs is an important task, e.g., predicting missing types of entities, predicting which molecules cause cancer, or predicting which drugs are promising treatment candidates. While black-box models often achieve high predictive performance, they are only post-hoc and locally explainable and do not allow the learned model to be easily enriched with domain knowledge. Towards this end, learning description logic concepts from positive and negative examples has been proposed. However, learning such concepts often takes a long time and state-of-the-art approaches provide limited support for literal data values, although they are crucial for many applications. In this paper, we propose EvoLearner - an evolutionary approach to learn ALCQ(D), which is the attributive language with complement (ALC) paired with qualified cardinality restrictions (Q) and data properties (D). We contribute a novel initialization method for the initial population: starting from positive examples (nodes in the knowledge graph), we perform biased random walks and translate them to description logic concepts. Moreover, we improve support for data properties by maximizing information gain when deciding where to split the data. We show that our approach significantly outperforms the state of the art on the benchmarking framework SML-Bench for structured machine learning. Our ablation study confirms that this is due to our novel initialization method and support for data properties.

CovidPubGraph: A FAIR Knowledge Graph of COVID-19 Publications - Pestryakova, Svetlana; Vollmers, Daniel; Sherif, Mohamed; Heindorf, Stefan; Saleem, Muhammad; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Scientific Data)

Einleitung - Janus, Richard; Schroeter-Wittke, Harald (Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren)

Kremers, Hermann (1860-1934) - Janus, Richard (Bauks)

Eingeständnis - Bekenntnis - Widerstand. Die Geste des Bekennens als Ende jeglichen Begehrens - Janus, Richard (Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren)

Pfingstmontag. Johannes 4, 19-26 - Janus, Richard (Er ist unser Friede. Lesepredigten 1. Advent 2022 bis Pfingstmontag 2023. Textreihe V/1)

Projektbericht zum durch die Forschungsreserve der Fakultät für Kulturwissenschaften geförderten Projekt „Hundegestütztes Resilienztraining – soziales Lernen von Kindern fördern“ - Mombeck, Mona Maria; Caruso, Carina

Tiergestützte Pädagogik - ein junges Feld in der Bildungswissenschaft - Mombeck, Mona Maria
Vortrag Arbeitskreis Schulbegleithunde [online]

Pfotenglück - Hunde in der Pädagogik - Mombeck, Mona Maria
Vortrag 50 Jahre UPB

Animal-Assisted Pedagogy & Animal Wellfare - Mombeck, Mona Maria
Vortrag Blue Cross [online]

Tiergestützte Pädagogik – Soziale Teilhabe – Inklusive Prozesse. Der Einsatz von Schulhunden aus wissenschaftlicher Perspektive - Mombeck, Mona Maria

Nutritional Assessment of Ready-to-Eat Salads in German Supermarkets: Comparison of the nutriRECIPE-Index and the Nutri-Score - Schlarbaum, Laura; Forner, Frank; Bohn, Kristin; Amberg, Michael; Mäder, Patrick; Lorkowski, Stefan; Meier, Toni (Foods)
Globally, an unbalanced diet causes more deaths than any other factor. Due to a lack of knowledge, it is difficult for consumers to select healthy foods at the point of sale. Although different front-of-pack labeling schemes exist, their informative value is limited due to small sets of considered parameters and lacking information on ingredient composition. We developed and evalauated a manufacture-independent approach to quantify ingredient composition of 294 ready-to eat salads (distinguished into 73 subgroups) as test set. Nutritional quality was assessed by the nutriRECIPE-Index and compared to the Nutri-Score. The nutriRECIPE-Index comprises the calculation of energy-adjusted nutrient density of 16 desirable and three undesirable nutrients, which are weighted according to their degree of supply in the population. We show that the nutriRECIPE-Index has stronger discriminatory power compared to the Nutri-Score and discriminates as well or even better in 63 out of the 73 subgroups. This was evident in groups where seemingly similar products were compared, e.g., potato salads (Nutri-Score: C only, nutriRECIPE-Index: B, C and D). Moreover, the nutriRECIPE-Index is adjustable to any target population’s specific needs and supply situation, such as seniors, and children. Hence, a more sophisticated distinction between single food products is possible using the nutriRECIPE-Index.

User Involvement in Training Smart Home Agents - Sieger, Leonie Nora; Hermann, Julia; Schomäcker, Astrid; Heindorf, Stefan; Meske, Christian; Hey, Celine-Chiara; Doğangün, Ayşegül (International Conference on Human-Agent Interaction)
Smart home systems contain plenty of features that enhance wellbeing in everyday life through artificial intelligence (AI). However, many users feel insecure because they do not understand the AI’s functionality and do not feel they are in control of it. Combining technical, psychological and philosophical views on AI, we rethink smart homes as interactive systems where users can partake in an intelligent agent’s learning. Parallel to the goals of explainable AI (XAI), we explored the possibility of user involvement in supervised learning of the smart home to have a first approach to improve acceptance, support subjective understanding and increase perceived control. In this work, we conducted two studies: In an online pre-study, we asked participants about their attitude towards teaching AI via a questionnaire. In the main study, we performed a Wizard of Oz laboratory experiment with human participants, where participants spent time in a prototypical smart home and taught activity recognition to the intelligent agent through supervised learning based on the user’s behaviour. We found that involvement in the AI’s learning phase enhanced the users’ feeling of control, perceived understanding and perceived usefulness of AI in general. The participants reported positive attitudes towards training a smart home AI and found the process understandable and controllable. We suggest that involving the user in the learning phase could lead to better personalisation and increased understanding and control by users of intelligent agents for smart home automation.
Keywords: human-agent interaction; smart homes; supervised learning; participation

Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

iMustHave. Anhand von Werbevideos den Kult um den digital global player Apple untersuchen - Bauer, Maike; Hohwiller, Peter (Der fremdsprachliche Unterricht Englisch)

Should I Stay or Should I Go? Discussing the Advantages and Disadvantages of Taking a Gap Year - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Virtual Employees in India: Off-site Employment for Large Corporations. Two oral exams - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Modern Slavery vs. Fairtrade: Raising Awareness of the Working Conditions in India - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Diaspora Short Stories – A Meaningful Aspect in Young Adult Literature? - Bauer, Maike

Computing generalizations of temporal ϵL concepts with next and global - Tirtarasa, Satyadharma; Turhan, Anni-Yasmin (SAC ’22: The 37th {ACM/SIGAPP} Symposium on Applied Computing, Virtual Event, April 25 - 29, 2022)

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) vom 09. bis 12.03.2022 in Köln - Janicki, Nicole

Efficient TBox Reasoning with Value Restrictions using the Flower Reasoner - Baader, Franz; Koopmann, Patrick; Michel, Friedrich; Turhan, Anni-Yasmin; Zarrieß, Benjamin (Theory Pract. Log. Program.)

Gott wird Mensch. Weihnachten zwischen Fiktion und Evangelium - Janus, Richard

Multilingual Verbalization and Summarization for Explainable Link Discovery - Fathi Ahmed, Abdullah; Ahmed Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Data Knowl. Eng.)

Applying Grammar-Based Compression to RDF - Röder, Michael; Frerk, Philip; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - 18th International Conference, ESWC 2021, Virtual Event, June 6-10, 2021, Proceedings)

Unsupervised Relation Extraction Using Sentence Encoding - Ali, Manzoor; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2021 Satellite Events - Virtual Event, June 6-10, 2021, Revised Selected Papers)

Unsupervised Relation Extraction Using Sentence Encoding - Ali, Manzoor; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2021 Satellite Events - Virtual Event, June 6-10, 2021, Revised Selected Papers)

InferNER: an attentive model leveraging the sentence-level information for Named Entity Recognition in Microblogs - Shahzad, Moemmur; Amin, Ayesha; Esteves, Diego; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Thirty-Fourth International Florida Artificial Intelligence Research Society Conference, North Miami Beach, Florida, USA, May 17-19, 2021)

Lemming - Example-based Mimicking of Knowledge Graphs - Röder, Michael; Thuy Sy Nguyen, Pham; Conrads, Felix; Alexandra Morim da Silva, Ana; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

SYNTHG: Mimicking RDF Graphs Using Tensor Factorization - Amer Desouki, Abdelmoneim; Conrads, Felix; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

A shallow neural model for relation prediction - Demir, Caglar; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

Template-based Question Answering using Recursive Neural Networks - G. Athreya, Ram; Kona Bansal, Srividya; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

LAUREN - Knowledge Graph Summarization for Question Answering - Jalota, Rricha; Vollmers, Daniel; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

Relicensing Combined Datasets - Wilke, Adrian; Bannoura, Arwa; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

ORCA - a Benchmark for Data Web Crawlers - Röder, Michael; de Souza, Geraldo; Kuchelev, Denis; Amer Desouki, Abdelmoneim; Ngonga Ngomo, Axel-Cyrille (15th IEEE International Conference on Semantic Computing, ICSC 2021, Laguna Hills, CA, USA, January 27-29, 2021)

Poster: Enabling Comparable and Reproducible Simulations for V2X Research - Hardes, Tobias; Logan, Dalisha; Sommer, Christoph; Klingler, Florian (13th IEEE Vehicular Networking Conference (VNC 2021))

Poster: Simulating Hybrid LEO Satellite and V2X Networks - Franke, Mario; Klingler, Florian; Sommer, Christoph (13th IEEE Vehicular Networking Conference (VNC 2021))

Dreidimensionale Oberflächenanalyse und Topografie-Simulation additiv hergestellter Laser-Sinter Bauteile - Delfs, Patrick
Anwendungen von Laser-Sinter Bauteilen als Sichtteile sind aufgrund der vergleichsweise schlechten Oberflächenqualität sehr begrenzt. In dieser Arbeit werden dreidimensionale Kennwerte benutzt, um die Oberflächenqualität von Laser-Sinter Bauteiloberflächen und die Einflüsse aus unterschiedlichen Bereichen der gesamten Prozesskette zu evaluieren. Beispielsweise wurden objektive Kennwerte, mit deren Hilfe Orangenhaut zu identifizieren ist, und Prozessparameter, die diese deutlich vermindern, gefunden. Mittels Durchführung von haptischen Versuchen wurde das subjektive Empfinden ermittelt und konnten zu objektiven Kennwerten korreliert werden. Eine mikroskopische Betrachtung des flachen Oberflächenwinkels mit verschieden farbigen Pulvern zeigt neue Erkenntnisse zum Anschmelzvorgang von Partikeln an die Schmelze. Zur nachträglichen Glättung von Oberflächen wurden mechanische, chemische und optische Nachbehandlungsmethoden verwendet und deren Potential aufgezeigt. Eine abschließende neuartige Simulation der dreidimensionalen Topografie bildet die Grundlage für ein Programm zur automatischen und funktionsgerechten Orientierung von Bauteilen, welche am Beispiel eines realen Bauteils erfolgreich validiert wurde. Zusammengenommen zeigen die Ergebnisse, dass die richtige Wahl von Bauorientierung und Prozessparametern entscheidend für die Bauteilqualität ist und selbst eine aufwendige Nachbearbeitung eine ungeschickte Wahl derer nur schwerlich ausgleichen kann.
Keywords: Additive Fertigung; Oberflächenqualität; 3D; Topografie; Simulation; PA12; Laser-Sintern; Rauheit

Erarbeitung eines methodischen Vorgehens zur merkmalspezifischen Charakterisierung der Verarbeitungseignung von nicht verstärkten und faserverstärkten Kunststoffen im Fused Deposition Modeling am Beispiel von Polyamid 6 - Schumacher, Christian
Das Fused Deposition Modeling (FDM) ist ein Verfahren zur additiven Fertigung (AF), welches von der Firma Stratasys Ltd. (früher Stratasys Inc.) kommerzialisiert wurde. Heute existieren auch FDM Maschinen anderer Hersteller. Im Gegensatz zu den Maschinen von Stratasys können bei diesen die Prozessparameter frei gewählt werden. Dadurch ist die Verarbeitung herstellerfremder Materialien möglich. Wie in allen AF-Verfahren, werden im FDM bestimmte Anforderungen an die zu verarbeitenden Materialien gestellt. Die Materialien sollten daher speziell für das FDM ausgewählt bzw. entwickelt werden. Die für eine gute Verarbeitbarkeit notwendigen Materialeigenschaften sind aktuell jedoch nicht hinreichend bekannt. Vielmehr sind auch keine Vorgehensweisen bekannt, um die Verarbeitungseignung verschiedener Materialien im FDM zu bewerten. Im Rahmen dieser Arbeit werden daher Vorgehensweisen vorgestellt, um die Verarbeitungseignung thermoplastischer Kunststoffe im FDM anhand bestimmter Merkmale zu bewerten. Die Schweißnahtqualität, der Bauteilverzug und die Gestaltungsfreiheit werden als wichtige Merkmale identifiziert. Unter Beachtung relevanter Einflussgrößen werden je Merkmal Probekörper und Prüfmethoden entwickelt, um merkmalspezifische Kennwerte zu definieren. Dadurch ist der Vergleich unterschiedlicher Materialien, unabhängig von der verwendeten Maschine und der Datenaufbereitung, möglich. Letztendlich werden verschiedene Materialmodifikationen auf Basis von PA 6 erstellt und mit Hilfe der vorgestellten Vorgehensweisen untersucht und bewertet.

On Biases in Online Reviews and the Moderating Effect of Review System Design - Neumann, Jürgen

Inferring Quality with Reputation Systems - Experimental Evidence on Elicitation Mechanisms and Aggregation Metrics - van Straaten, Dirk

Models and Algorithms for Hybrid Networks and Hybrid Programmable Matter - Hinnenthal, Kristian

Johannes Görbert, Nikolas Immer (Hg.): Ambulante Poesie. Explorationen deutschsprachiger Reiselyrik seit dem 18. Jahrhundert, Berlin, Boston: de Gruyter 2020. - Elit, Stefan (Zeitschrift für deutsche Philologie)

Laborpraktika auf Distanz. Ansätze in den Naturwissenschaften - Bauer, Anna; Sacher, Marc; Habig, Sebastian; Fechner, Sabine (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)

Studierende der Berufs-und Wirtschaftspädagogik: (Un-)bekannte Wesen? - Grunau, Janika; Jenert, Tobias (bwpat Spezial)

Berücksichtigung Selbstorganisierender Produktionssysteme in frühen Phasen der interdisziplinären Produktentwicklung - Hentze, Julian
Der Wandel in der industriellen Produktion durch die Rahmenbedingungen der vierten industriellen Revolution eröffnet neue Wege für Produkt- und Produktionstechnologien. Produktionssysteme, welche selbstorganisiert, dezentral und flexibel gestaltet werden können, verändern auch die Rahmenbedingungen für das entwicklungsmethodische Vorgehen der Produkte. Neben der zunehmenden Interdisziplinarität müssen Methoden zur Unterstützung für die Produktentwicklung erarbeitet werden, um eine effektive und effiziente Entwicklung trotz veränderter oder zusätzlicher Rahmenbedingungen gewährleisten zu können.Die vorliegende Arbeit fokussiert den Anwendungsfall Selbstorganisierender Produktionssysteme (SOPS). Die interdisziplinäre Produktentwicklung für mechatronische und cyber-physische Systeme mit dem V-Modell der VDI Richtlinie 2206, wird um eine Methode zur Berücksichtigung Selbstorganisierender Produktionssysteme in frühen Phasen der interdisziplinären Produktentwicklung (CoSOPS) erweitert. Die Methode ermöglicht für den spezifischen Anwendungsfall der SOPS sowohl die strategische als auch die produktbezogene und entwicklungsbegleitende Analyse der individuellen Potenziale für die Nutzung von SOPS. Dazu wurden in der Arbeit konkrete Anforderungen an die Methode sowie Einflüsse der SOPS auf die Produktentwicklung erarbeitet und analysiert. Die neue Methode CoSOPS wird detailliert ausgearbeitet und die Ergebnisse in einer strukturierten Evaluation validiert.

On testing transitivity in online preference learning - Haddenhorst, Björn; Bengs, Viktor; Hüllermeier, Eyke (Machine Learning)
Abstract The efficiency of state-of-the-art algorithms for the dueling bandits problem is essentially due to a clever exploitation of (stochastic) transitivity properties of pairwise comparisons: If one arm is likely to beat a second one, which in turn is likely to beat a third one, then the first is also likely to beat the third one. By now, however, there is no way to test the validity of corresponding assumptions, although this would be a key prerequisite to guarantee the meaningfulness of the results produced by an algorithm. In this paper, we investigate the problem of testing different forms of stochastic transitivity in an online manner. We derive lower bounds on the expected sample complexity of any sequential hypothesis testing algorithm for various forms of stochastic transitivity, thereby providing additional motivation to focus on weak stochastic transitivity. To this end, we introduce an algorithmic framework for the dueling bandits problem, in which the statistical validity of weak stochastic transitivity can be tested, either actively or passively, based on a multiple binomial hypothesis test. Moreover, by exploiting a connection between weak stochastic transitivity and graph theory, we suggest an enhancement to further improve the efficiency of the testing algorithm. In the active setting, both variants achieve an expected sample complexity that is optimal up to a logarithmic factor.

Dark triad managerial personality and financial reporting manipulation - Mutschmann, Martin; Hasso, Tim; Pelster, Matthias (Journal of Business Ethics)

Resistivity and Formation of Intermetallic Layer in Aluminum-Steel Clad Strip - Křivská, B; Šlapáková, M; Králík, R; Bajtošová, L; Cieslar, M; Grydin, Olexandr; Stolbchenko, M; Schaper, Mirko (IOP Conference Series: Materials Science and Engineering)

Dämpfungseigenschaften geklebter Verbindungen - Potenzialanalyse und Klebstoffcharakterisierung - Göddecke, Johannes; Meschut, Gerson; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas (adhäsion KLEBEN & DICHTEN)